2011
DOI: 10.1002/oa.1099
|View full text |Cite
|
Sign up to set email alerts
|

A possible case of ‘poll‐evil’ in an early Scythian horse skull from Arzhan 1, Tuva Republic, Central Asia

Abstract: Occipital bone lesions on an Iron Age horse cranium from the burial mound of Arzhan 1, Tuva, Central Asia, are described and interpreted. Cavitations around the nuchal ligament attachment site on the skull are interpreted as foci of inflammation and necrosis following local infection. It is suggested that the pathology represents a case of ‘poll‐evil’, most likely due to a bacterial infection. The significance of such an interpretation is discussed, including its implications for disease ecology and the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Authors discussed that this case may be due to B. abortus the common cause of poll evil in horses. Thus this study shows that the pathogen existed long back causing poll evil in horses (Bendrey et al, 2011).…”
Section: Poll Evil and Fistulous Withersmentioning
confidence: 64%
See 1 more Smart Citation
“…Authors discussed that this case may be due to B. abortus the common cause of poll evil in horses. Thus this study shows that the pathogen existed long back causing poll evil in horses (Bendrey et al, 2011).…”
Section: Poll Evil and Fistulous Withersmentioning
confidence: 64%
“…These fistulas may heal slowly and there are always chances that they reappear (Cohen et al, 1992). Few years back researchers have found an Iron Age horse cranium from Tuva Republic, Central Asia and the cranium had occipital lesions, cavities around the nuchal ligament attachment site was noted in the skull which may be due to inflammation followed by necrosis (Bendrey et al, 2011). The researchers concluded that condition is poll evil originating due to bacterial cause.…”
Section: Poll Evil and Fistulous Withersmentioning
confidence: 98%
“…Bendrey et al . 2011), nuchal enthesopathy appears to be commonly caused by habitual activity such as horseback riding (Figure 2a). Despite this interesting pattern, Bendrey concluded that nuchal pathologies had limited utility for archaeological identification of horse use, as age dependency was a major concern (Bendrey 2008: 30).…”
Section: Archaeozoological Identification Of Riding and Chariotrymentioning
confidence: 99%
“…As with fistula withers, both brucellosis and actinomycosis have been associated with this condition. However, a traumatic injury of the poll region can also lead to inflammation and resulting osseous lesions (Bendrey, Cassidy, Bokovenko, Lepetz, & Zaitseva, 2009).…”
Section: Results: the Nonhuman Remains (Abgs)mentioning
confidence: 99%